2020
DOI: 10.3390/ijms21041533
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Hepatic Metabolic Defects Induced by beclin1 Heterozygosity in Adult Zebrafish

Abstract: Hepatic disorders have been increasing in recent years because of high carbohydrate diets. Hepatocytes depend mainly on the basal autophagy to maintain hepatic glucose/lipid homeostasis in mammals. However, the regulatory mechanisms of autophagy in hepatic energy metabolism are still unknown in fish species. Accordingly, mutant zebrafish lines of autophagy-related genes beclin1 and atg7 were generated by CRISPR/Cas9 gene-editing technology. Interestingly, unlike atg7+/−, male beclin1+/− zebrafish displayed liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…After centrifugation at 12,000× g round per minute (RPM) for 20 min at 4 °C, the supernatant was collected carefully. The procedure was managed according to previous reports [ 37 ]. After electrophoresis and electrotransfer, Nylon Fluoride (PVDF) membranes (Millipore, Burlington, MA, USA) were cut, blocked against Bovine Serum Albumin (5% BSA, AUG pharma, Giza, Egypt), resolved in Tris Buffered Saline with Tween (TBST) before one hour and then blotted with primary antibodies all night.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 12,000× g round per minute (RPM) for 20 min at 4 °C, the supernatant was collected carefully. The procedure was managed according to previous reports [ 37 ]. After electrophoresis and electrotransfer, Nylon Fluoride (PVDF) membranes (Millipore, Burlington, MA, USA) were cut, blocked against Bovine Serum Albumin (5% BSA, AUG pharma, Giza, Egypt), resolved in Tris Buffered Saline with Tween (TBST) before one hour and then blotted with primary antibodies all night.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish mutant lines have shown that becn1 is essential for autophagy, as knock-out mutants for this gene die at the larval stage [100]. In addition, mutants in becn1 and atg7 have outlined the importance of becn1 for maintaining homeostasis of nutrient metabolism and in liver development [101].…”
Section: Macroautophagy In Teleost Fishmentioning
confidence: 99%
“…Studies in mice with liver‐specific knockout of autophagy found that autophagy is essential for maintaining blood glucose and amino acid levels (Ezaki et al., 2011). In adult zebrafish, impaired autophagy in the liver leads to a disturbance in glucose/lipid metabolism and negatively regulates apoptosis accompanied by the induction of cellular proliferation and an acute inflammatory response (Mawed et al., 2020). However, the regulatory mechanisms of autophagy in hepatic energy metabolism are still obscure in fish species.…”
Section: Introductionmentioning
confidence: 99%